ANALISIS KUALITAS SISTEM ONLINE SINGLE SUBMISSION RISK BASE APPROACH DALAM PELAYANAN KESESUAIAN KEGIATAN PEMANFAATAN RUANG PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN SUMBAWA BARAT - FARHANA, ANA; UMAR, UMAR; SUBARI, SUBARI (Universitas Mahasaraswati K. Mataram, 2023)
The aims of this research are; 1) to determine the quality of the Suitability of Space Utilization Activities service in West Sumbawa Regency and 2) to analyze Partner Perceptions regarding the Implementation of the Online Single Submission Risk Base Approach System in the Suitability of Space Utilization Activities Service in West Sumbawa Regency. This research uses descriptive qualitative research methods. Data collection techniques were carried out through observation and interviews with research informants. Data were analyzed using a qualitative analysis approach. Based on the data obtained, the research results show that; 1) From the five measurements of KKPR service quality, it can be seen that the quality of KKPR services in West Sumbawa Regency plays a central role in sustainable development and community welfare. From the five analysis of partner perceptions regarding the implementation of the OSS RBA System in KKPR services to reduce bureaucracy and increase accessibility, speed up the licensing process, and increase transparency.